Conceptual Study of The Phenomenon of Celebrity Private Life in The Perspective of Media Audiences - Pramesthi, Jasmine Alya; Dewanti, Inke Nur; Muhammad, Haris; Afrianto, Adrian Pratama (Universitas Pendidikan Nasional, 2024)
Audiences in the media are viewed through two perspectives, namely passive audiences, and active audiences. Through the following conceptual paper, the author reviews the two perspectives of the media audience with the personal life cases of celebrity couples who are consumed by the media and the activeness of the audience in responding to the formation of fandom of the couple. the active one. The media audience is considered a commodity that is carried out by the media for news or TV programs regarding the pair Lesti Kejora and Rizky Billar. The audience in this phenomenon also contributes to the formation of the personal image of celebrities Lesti Kejora and Rizky Billar as audience objects in the mass media, the phenomenon that occurs is a communication strategy that appears to build public opinion. In contrast to these assumptions, there is an idea that the audience has the authority to choose the media regarding the couple and the authority to join a virtual community of Leslar fandom. Active audiences can provide interpretive and respond to the media content they choose. If it is examined more deeply, this can also be a criticism of the media because it raises anti-mainstream phenomena for public consumption, especially when viewed from the perspective of uses and gratification. This study is expected to be able to contribute knowledge about the perspective of media audiences in more depth, especially how the audience's perspective on the phenomenon of celebrity personal life. Further research on the two perspectives of the media audience in other research methodologies using interpretive or scientific can also enrich the study of media audiences.